ANKRD22 aggravates sepsis-induced ARDS and promotes pulmonary M1 macrophage polarization - Zhang, Shi; Liu, Yao; Zhang, Xiao-Long; Sun, Yun; Lu, Zhong-Hua (Journal of translational autoimmunity (Online), 2024)
Acute respiratory distress syndrome (ARDS) is independently associated with a poor prognosis in patients with sepsis. Macrophage M1 polarization plays an instrumental role in this process. Therefore, the exploration of key molecules affecting acute lung injury and macrophage M1 polarization may provide therapeutic targets for the treatment of septic ARDS. Here, we identified that elevated levels of Ankyrin repeat domain-containing protein 22 (ANKRD22) were associated with poor prognosis and more pronounced M1 macrophage polarization in septic patients by analyzing high-throughput data. ANKRD22 expression was also significantly upregulated in the alveolar lavage fluid, peripheral blood, and lung tissue of septic ARDS model mice. Knockdown of ANKRD22 significantly attenuated acute lung injury in mice with sepsis-induced ARDS and reduced the M1 polarization of lung macrophages. Furthermore, deletion of ANKRD22 in macrophages inhibited M1 macrophage polarization and reduced levels of phosphorylated IRF3 and intracellular interferon regulatory factor 3 (IRF3) expression, while re-expression of ANKRD22 reversed these changes. Further experiments revealed that ANKRD22 promotes IRF3 activation by binding to mitochondrial antiviral-signaling protein (MAVS). In conclusion, these findings suggest that ANKRD22 promotes the M1 polarization of lung macrophages and exacerbates sepsis-induced ARDS.